2020
DOI: 10.3390/geosciences10090355
|View full text |Cite
|
Sign up to set email alerts
|

Soil Heating at High Temperatures and Different Water Content: Effects on the Soil Microorganisms

Abstract: Soil properties determining the thermal transmissivity, the heat duration and temperatures reached during soil heating are key factors driving the fire-induced changes in soil microbial communities. The aim of the present study is to analyze, under laboratory conditions, the impact of the thermal shock (infrared lamps reaching temperatures of 100 °C, 200 °C and 400 °C) and moisture level (0%, 25% and 50% per soil volume) on the microbial properties of three soil mixtures from different sites. The results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…Temperature sensitivity of interactions between microbes has also been discovered in many different natural communities. In soil, short-term extreme heat shock (>100 • C) has been shown to cause a long-term reduced growth of the treated microbial communities persisting for multiple generations (Barreiro et al, 2020). More moderate long-term alterations of growth temperature in Alpine soils have shown that these soil communities have a growth optimum between 27 and 30 • C and that the community structure was substantially altered, in accordance with the findings in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Temperature sensitivity of interactions between microbes has also been discovered in many different natural communities. In soil, short-term extreme heat shock (>100 • C) has been shown to cause a long-term reduced growth of the treated microbial communities persisting for multiple generations (Barreiro et al, 2020). More moderate long-term alterations of growth temperature in Alpine soils have shown that these soil communities have a growth optimum between 27 and 30 • C and that the community structure was substantially altered, in accordance with the findings in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Network parameters thus suggest that heat stress reduces the robustness and stability of tick microbial communities. Shifts on microbial interaction patterns as result of temperature variation has been previously described in soil bacterial communities [3,8,13,20,54].…”
Section: Discussionmentioning
confidence: 70%
“…Because soil chemistry is influenced by many factors, such as organic matter input and environmental factors, our results are only a snapshot of the soil conditions at the time of sampling. When it comes to microbial‐driven soil processes, temperatures reached during the experimental fire at the surface may have been high enough to inhibit microbial growth close to the surface (Bárcenas‐Moreno & Bååth, 2009; Barreiro et al, 2020). However, microbial growth recovers rapidly, in response to increased nutrients availability and C from dead organisms after fire (Bárcenas‐Moreno & Bååth, 2009; Barreiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to microbial‐driven soil processes, temperatures reached during the experimental fire at the surface may have been high enough to inhibit microbial growth close to the surface (Bárcenas‐Moreno & Bååth, 2009; Barreiro et al, 2020). However, microbial growth recovers rapidly, in response to increased nutrients availability and C from dead organisms after fire (Bárcenas‐Moreno & Bååth, 2009; Barreiro et al, 2020). The impacts of fire on microbial growth and biomass are determined by the residence time of high temperatures rather than the maximum temperature (Lombao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%